Research on the Relationship between Higher Education Employment Evaluation and Innovation and Entrepreneurship (Lex localis - Journal of Local Self-Government, 2025)
Employment assessment and innovation and entrepreneurship education have become a crucial measure for evaluating the quality of university education. This paper analyzes the current state of employment assessment and innovation and entrepreneurship education in Chinese higher education institutions. It points out that the current employment assessment system is overly simplistic, that innovation and entrepreneurship education is disconnected from actual needs, and that policy incentives have not been fully implemented. Through data analysis, the paper explores the intrinsic relationship between innovation and employment assessment in higher education. The study finds that strengthening innovation and entrepreneurship education can effectively enhance employment assessment in higher education. Based on these findings, the paper proposes optimization strategies. It recommends constructing a multidimensional employment assessment system, integrating innovation and entrepreneurship education into the entire process of talent cultivation, strengthening institutional safeguard mechanisms, and achieving synchronous improvement in high-quality employment and educational quality.